Essential Oil and Juice from Bergamot and Sweet Orange Improve Acne Vulgaris Caused by Excessive Androgen Secretion - Peng Sun; Liang Zhao; Nanhai Zhang; Chengtao Wang; Wei Wu; Arshad Mehmood; Liebing Zhang; Baoping Ji; Feng Zhou (Mediators of Inflammation)
Acne vulgaris is one of the most common chronic inflammatory skin diseases. Bergamot and sweet orange are rich in nutritional and functional components, which exhibit antioxidant, anti-inflammatory, and antiapoptotic effect. The aim of this study was to evaluate the potential effect of bergamot and sweet orange (juice and essential oil) on acne vulgaris caused by excessive secretion of androgen. Eighty male golden hamsters were randomly divided into 10 groups and received low or high dose of bergamot and sweet orange juice and essential oil, physiological saline, and positive drugs for four weeks, respectively. Results showed that all interventions could improve acne vulgaris by reducing the growth rate of sebaceous gland spots, inhibiting TG accumulation, decreasing the release of inflammatory cytokines (notably reducing IL-1α levels), promoting apoptosis in the sebaceous gland, and decreasing the ratio of T/E2. Among them, bergamot and orange essential oil may have better effects (dose dependent) on alleviating acne vulgaris than the corresponding juice. In view of the large population of acne patients and the widespread use of sweet orange and bergamot, this study is likely to exert an extensive and far-reaching influence.